L'étanchéité de l'A.A.N.B. est-elle menacée? - Bonenfant, Jean-Charles (Les Cahiers de droit, 1977)
In his opinion in John A. MacDonald, Railquip Enterprises Ltd and Vapor Canada Limited, Chief Justice Laskin commented that in the future it might be necessary to reconsider the 1937 Labour Conventions Decision which established the « watertight compartments » doctrine applicable to the implementation of treaties concluded by Canada. According to this doctrine as it was set forth by the Privy Council, the fact that Canada can enter into treaties with other countries does not mean that the Federal Parliament of Canada can legislate contrary to the distribution of powers provided for by sections 91 and 92 of the British North America Act. In his article, Professor Bonenfant recalls the criticism which the Privy Council evoked, particularly that which appeared in the June, 1937, issue of The Canadian Bar Review. If the Supreme Court of Canada wishes to revise the decision of the Privy Council, it will not be hampered by the rule of stare decisis. But, Professor Bonenfant writes, whatever the judicial solution may be, it would probably be better to follow the example of other countries, particularly the example provided by article 32 of the Constitution of the German Federal Republic, and seek a political solution. In this domain as in others, if federalism has failed in Canada, he writes that it is perhaps because the interpretation of Canada's Constitution has been left to the intellectual virtuosity of the members of the Privy Council and of the Supreme Court.